2003
DOI: 10.1038/sj.onc.1207332
|View full text |Cite
|
Sign up to set email alerts
|

Secretion of cytokines and growth factors as a general cause of constitutive NFκB activation in cancer

Abstract: The constitutive activation of nuclear factor jB (NFjB) helps a variety of tumors to resist apoptosis and desensitizes them to chemotherapy, but the causes are still largely unknown. We have analysed this phenomenon in eight mutant cell lines derived from human 293 cells, selected for NFjB-dependent expression of a marker gene, and also in seven tumor-derived cell lines. Conditioned media from all of these cells stimulated the activation of NFjB (up to 30-fold) in indicator cells carrying an NFjB-responsive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
73
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 47 publications
3
73
0
Order By: Relevance
“…Several studies in recent years have shown that autocrine production of cytokines confers constitutive NF-B activity in colon, prostate, pancreatic, and other types of cancer (53). Our recent results reveal that the constitutive activation of NF-B in most of the mutants is caused by deregulated expression of secretion of cytokines and other ligands, and some of these have been identified (54). Although the loss of cytoplasmic negative regulators such as SODD, CARD-inhibitor of NF-Bactivating ligands, apoptosis signal-regulating kinase 1, rafkinase inhibitor protein, PKC-interacting cousin of thioredoxin (PICOT), and phosphatase and tensin homolog (PTEN) might also result in the constitutive activation of NF-B, we find that SODD, PICOT, and PTEN are not missing in our constitutive mutants.…”
Section: Discussionmentioning
confidence: 53%
“…Several studies in recent years have shown that autocrine production of cytokines confers constitutive NF-B activity in colon, prostate, pancreatic, and other types of cancer (53). Our recent results reveal that the constitutive activation of NF-B in most of the mutants is caused by deregulated expression of secretion of cytokines and other ligands, and some of these have been identified (54). Although the loss of cytoplasmic negative regulators such as SODD, CARD-inhibitor of NF-Bactivating ligands, apoptosis signal-regulating kinase 1, rafkinase inhibitor protein, PKC-interacting cousin of thioredoxin (PICOT), and phosphatase and tensin homolog (PTEN) might also result in the constitutive activation of NF-B, we find that SODD, PICOT, and PTEN are not missing in our constitutive mutants.…”
Section: Discussionmentioning
confidence: 53%
“…Furthermore, recent data suggest that in a variety of tumors, several NFkB target genes encode secreted growth factors that induce NFkB activation. 64 Thus, autocrine loops might be also important in the constitutive activation of NFkB in cancer. In this work, clinical studies demonstrated a higher incidence of recurrence and fatal outcome among patients in which a coordinated increase in the expression and activation of the above-mentioned proteins was observed.…”
Section: Angiogenesis In Hematologic Malignanciesmentioning
confidence: 99%
“…In fact, the relA insertional mutant has already provided important evidence for a positive-feedback loop involving secreted factors and NF-B. We have previously reported that elevated secretion of certain growth factors can cause constitutive NF-B activation in many cancer cell lines, and probably, also in tumors (13,14). Others have reported that Ap1 causes elevated growth factor secretion and the ensuing activation of NF-B which, in turn, cooperates with Ap1 (25).…”
Section: Discussionmentioning
confidence: 97%
“…Because several different cytokines are under NF-B transcriptional control, a positive-feedback loop can be established. We used an NF-B reporter cell line (13) to test whether medium conditioned by the mutant clones contains NF-Bactivating factors. Treatment of the reporter cells with medium conditioned by 3B22͞35 cells caused a robust elevation of luciferase activity (Fig.…”
Section: Reversible Promoter-insertion Mutagenesis Of Nf-b-dependent mentioning
confidence: 99%
See 1 more Smart Citation